2017
DOI: 10.1002/wat2.1243
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying components of the phosphorus cycle in temperate forests

Abstract: We review the state-of-the-art of cross-disciplinary knowledge on phosphorus (P) cycling in temperate forest ecosystems, focused at studies from hydrology, biology, biogeochemistry, soil-, and geosciences. Changes in soil P stocks during long-term ecosystem development are addressed briefly; the general ranges of specific P pools and P fluxes within the ecosystem and the presumed underlying processes are covered more in depth. Wherever possible, we differentiate between coniferous and deciduous forests. As the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 503 publications
(868 reference statements)
8
52
2
Order By: Relevance
“…Furthermore, P available in the upper mineral soil (0.02 mg/g, see Table 2) at our sites appears to be relatively low compared with averages for coniferous (0.84 mg/g) or deciduous (0.98 mg/g) temperate forests (Sohrt, Lang, & Weiler, 2017). Furthermore, P available in the upper mineral soil (0.02 mg/g, see Table 2) at our sites appears to be relatively low compared with averages for coniferous (0.84 mg/g) or deciduous (0.98 mg/g) temperate forests (Sohrt, Lang, & Weiler, 2017).…”
Section: Leaf Litter Elemental Composition: a Proxy Of Ecosystem Nucontrasting
confidence: 54%
“…Furthermore, P available in the upper mineral soil (0.02 mg/g, see Table 2) at our sites appears to be relatively low compared with averages for coniferous (0.84 mg/g) or deciduous (0.98 mg/g) temperate forests (Sohrt, Lang, & Weiler, 2017). Furthermore, P available in the upper mineral soil (0.02 mg/g, see Table 2) at our sites appears to be relatively low compared with averages for coniferous (0.84 mg/g) or deciduous (0.98 mg/g) temperate forests (Sohrt, Lang, & Weiler, 2017).…”
Section: Leaf Litter Elemental Composition: a Proxy Of Ecosystem Nucontrasting
confidence: 54%
“…The BD of P in the study area was higher than reported for a small number of forest sites in Bol et al () of 7–33 mg/(m 2 year), the mean values for coniferous and deciduous forests of the temperate zone of 38 ± 51 and 57 ± 107 mg/(m 2 year), respectively, compiled in Sohrt et al (), and two sites in Central and South America of 19 mg/(m 2 year) (Tipping et al, ), illustrating that considerable P inputs reached the study ecosystem (Figure ). Our estimated DD of P was higher than the 88 mg/(m 2 year) reported from the Taï tropical rainforest in Côte d'Ivoire attributed to Harmattan dust (Stoorvogel et al, ).…”
Section: Discussionmentioning
confidence: 53%
“…Low weathering rates at our study site were also reflected by the finding that the export of dissolved P with ST ( Figure 1) was at the lower end of the range of 1-1,300 mg/(m 2 year) reported for several temperate and tropical forested catchments (Figure 1; Bol et al, 2017). When the extreme value of 1,300 mg/(m 2 year) · m −2 · year −1 in Bol et al (2017) was disregarded, our export of dissolved P with ST fell in the middle of the reported range of 1-60 mg/(m 2 year) and it was slightly higher than the mean export rates of P with ST from temperate catchments under coniferous (11 ± 20 mg/(m 2 year) and deciduous forest (12 ± 20 mg/(m 2 year) ; Sohrt et al, 2017). The export of P with TSPs ( Figure 1) was much lower than in a study of Meyer and Likens (1979) in a temperate forest, where 800 mg/(m 2 year) P were exported with fine particles.…”
Section: 1029/2018jg004942mentioning
confidence: 67%
“…While an increase in leaching can explain the decrease of nitrogen availability, the link between climate and phosphorus availability might be more complex than our hypotheses suggest. Long‐term soil development processes, differences in phosphorus deposition or intraspecific tree litter quality responses to climate, that is links that we did (and could) not include in any of the hypothesized models, may have driven the observed phosphorus availability responses to climate (Sohrt, Lang, & Weiler, ).…”
Section: Discussionmentioning
confidence: 99%